The Role Of Work-Life Balance And Emotional Intelligence On Coffee Shop Employee Performance In Pontianak City - Alvin; Nova Arestia (LP2M IAIN Palopo, 2026)
This study aims to determine the roles of work-life balance and emotional intelligence on the performance of coffee shop employees in Pontianak. This study employs a quantitative data-based approach with a survey method. Data analysis was conducted through several testing criteria, including validity, reliability, classical assumption tests, multiple linear regression, F-test, and T-test, utilizing IBM SPSS version 26 software. The study involved 180 employees distributed across various coffee shops in Pontianak who met the requirements for multivariate sampling techniques. The results indicate that both variables—work-life balance and emotional intelligence—have a positive and significant impact on improving employee performance. The findings further emphasize that maintaining a balance between work and personal life, combined with effective emotional management, significantly assists employees in working effectively.